Modified kraft lignin for bioremediation applications - Santos, Diva A. Simões dos (2019)
Kraft lignin (KL) from industrial pulping of E. globulus wood was subjected to the oxidative modification with the aim to produce sorbent mimicking humic matter for the bioremediation purposes. Lignin was oxidized by polyoxometalate Na(5)[PMo(10)V(2)O(40)] (POM), solely or in the presence of laccase, under pre-selected aerobic conditions (50-60°C, 1-2h, oxygen pressure 5 bar). The most pronounced lignin oxidation without its depolymerisation was observed in the reaction system POM/O(2). Modified lignins possessed increased amounts of COOH (up to 15 %) and CO (up to 500 %) groups, when compared to unmodified KL, and significantly higher molecular weights. Sorption capacity of KL before and after modification towards transition metals (cadmium (II) and mercury (II)) and triazine pesticide (atrazine) was assessed in batch experiments under equilibrium conditions. KL oxidation improved sorption capacity towards transition metals (up to 15 %) but not necessarily the uptake of atrazine that was higher for unmodified KL.